The role of religious communication in North Sumatra's governmental institutions - Fahri Azhari; Lahmuddin; Hasnun Jauhari Ritonga (Faculty of Communications Science, Dr. Soetomo University, 2023)
This study aims to examine how the Department of Youth and Sports in North Sumatra utilises religious communication to enhance the well-being of young individuals. It contributes to scholarly knowledge by shedding light on the strategies employed by the Department to improve youth quality through Islamic communication. The study employs field methodologies and applies Miles and Huberman's data analysis model. The findings are divided into three key dimensions: 1) Planning Islamic Communication: Analysing the Department's Strategies for Effective Communication in an Islamic Context; 2) Organising and Implementing Islamic Communication: Investigating the Department's Efforts in Organising and Executing Islamic Communication Initiatives Targeting North Sumatra's Youth; and 3) Monitoring and Evaluating Islamic Communication: Assessing the Department's Systematic Evaluation of the Effectiveness of Islamic Communication Strategies in Youth Engagement. Additionally, this study encounters challenges related to technology and semantics. Semantic difficulties arise from varying interpretations and analyses of Islamic communication messages among the youth population, while technical obstacles include concerns regarding infrastructure deficiencies and resource constraints.